High order plasmonic vortex generation based on spiral nanoslits - Jing Fang; Changda Zhou; Zhen Mou; Shuyun Wang; Jiayi Yu; Yuanjie Yang; Gregory J Gbur; Shuyun Teng; Yangjian Cai (New Journal of Physics, 2021)
Highly localized plasmonic vortices carrying orbital angular momentum are of importance for many applications. Yet, it is a challenge to generating plasmonic vortex with a high topological charge because of no available technique. Here, a novel plasmonic vortex generator is proposed based on spiral nanoslits etched in a metal film, which can produce a high order plasmonic vortex. The consecutive spiral nanoslit can generate plasmonic vortex with high intensity and the segmented nanoslits enhances the controllability of the plasmonic vortex, which are demonstrated numerically and experimentally. High order plasmonic vortex generation will broaden the prospects for plasmonic vortices in practical applications for nanomanipulation and nanofabrication.